Analisis Karakteristik Emisi Gas Buang Pada Sarana Transportasi Roda Dua Kota Banda Aceh - - Jalaluddin; Asri Gani; - Darmadi (Jurnal Teknik Mesin Unsyiah, 2013)
The study was conducted to measure exhaust emissions and describe the level of air pollution from motorcycles operating in Banda Aceh and and surrounding areas. The measurement of exhaust emissions is done when the engine starts with the average gas pressure between 3000 - 4000 rpm and the motorcycle is in stationary condition, as well as air conditioning in the cabin is off. The measurement parameter is Carbon Dioxide CO2 ( % ) , Carbon Monoxide CO ( mg/m3 ) , Nitrogen Dioxide NO2 ( mg/m3 ) , and Sulful Dioxide SO2 ( mg/m3 ) and the emission gauge used is Quintox flue Gas Analyzer. Based on the results of the study of the level of CO2 produced by motorcycles of various cylinder capacities are 12 % below quality standards. The level of O2 generated in the combustion process of the motorcycles is far above 2% and 1050mg/m3 of SO2. The level of SO2 exshausted is 2% above the quality standard of SO2 set in the Regulation of the Minister of Environment , which is 800 mg/m3.